Impact of Destination Attributes on Tourists Destination Selection: With Special Reference to Cultural Triangle of Sri Lanka - Raazim, Mohamed A. M.; Munasinghe, Munasinghege A. T. K. (ASEAN Journal on Hospitality and Tourism, 2021)
Sri Lanka is one of the fastest-growing tourist destinations in the world. Amongst tourists’ attractions, “Cultural Triangle”, a region of the cultural heritage of the country has become the highest income generating destination. However, when compared with the other tourists’ destinations of the country, the number of tourists visiting the cultural triangle is low. As the literature reveals, the attributes of the destination matter in destination selection by the international tourists. Thus, considering the importance of this region as the top income contributor but not in terms of the number of tourists’ visits, this study problematizes the impacts of destination attributes on tourist`s destination selection. Accordingly, the objective of this study is to identify the destination attributes and their relationship with the tourists’ destination selection decisions. Data was collected through questionnaires from a sample of 222 foreign tourists who visited the cultural triangle during 2019 through a selected travel agent. Results of the multiple regression analysis revealed that attributes of Amenities, Destination Attractions, Accessibility, Ancillary Services, and Destination Environment as having a moderate positive relationship whilst, the service quality weak positive relationship with Tourist’s Destination selection. Destination attraction was identified as the most influential factor of all attributes. The findings of this study can be used by policymakers in developing destinations for tourists’ attractions in the country.